Nonelective hospital admissions, discharge disposition, and health services utilization in epilepsy patients: A population‐based study. (18th August 2020) - Kwon, Churl‐Su; Wong, Bonnie; Agarwal, Parul; Lin, Jung‐Yi; Mazumdar, Madhu; Dhamoon, Mandip; Jetté, Nathalie
Abstract: Objective: Identifying adverse outcomes and examining trends and causes of nonelective admissions among persons with epilepsy would be beneficial to optimize patient care and reduce health services utilization. We examined the association of epilepsy with discharge status, in‐hospital mortality, length‐of‐stay, and charges. We also examined 10‐year trends and causes of hospital admissions among those with and without epilepsy. Methods: Nonelective hospital admission in persons with epilepsy was identified in the 2005‐2014 National Inpatient Sample (NIS) using a validated International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM) case definition. The NIS is the largest US all‐payer database including patient and hospital‐level variables, and represents hospitalizations in the general population. Descriptive statistics on trends and causes of admissions and multivariable regression analysis summarizing the association of epilepsy with the outcomes of interest are presented. Results: Of 4 718 178 nonelective admissions in 2014, 3.80% (n = 179 461) were in persons with epilepsy. Admissions in persons with epilepsy increased from 14 636 to 179 461 ( P < .0001) between 2005 and 2014. As compared to persons without epilepsy, hospital admissions in persons with epilepsy had higher odds of transfer to other facilities (odds ratio [OR] = 1.77, 95% confidence interval [CI]: 1.72‐1.81, P < .0001), being discharged against medical advice (OR = 1.48, 95% CI: 1.38‐1.59, P < .0001), and incurring 4% greater total charges ( P < .0001). Epilepsy, convulsions, pneumonia, mood disorders, cerebrovascular disease, and septicemia were the top causes for admissions in those with epilepsy. Significance: Future research should focus on designing targeted health care interventions that decrease the number of hospital admissions, reduce health services utilization, and increase the odds of discharge home in people with epilepsy.